Analisis Rational Choice Theory dalam Pekerja Seks Komersial (PSK) di Pasar Kembang Yogyakarta - Devi Wulandari; Untung Sumarwan (Universitas Budi Luhur, 2023)
This thesis discusses the analysis of Rational Choice Theory in Commercial Sex Workers (CSWs) inPasar KembangYogyakarta and analyzed with Rational Choice Theory. The phenomenon of commercialsex workers that occurred in Pasar Kembang Gedong Tengen, Yogyakarta, was motivated by theurgency of the necessities of life, economy, and lifestyle. This is because working as a prostitute doesnot require complicated requirements, thus making them undertake the profession. This profession isconsidered an instant job and can generate a large income without having to tire of working all day.Rational Choice Theory sees perpetrators consider each characteristic of a potential crime(opportunities, costs and benefits). There are many reasons why the woman chose to prostitute herself.The result of these pressures is the defeat of internal factors such as thoughts, reasoning, and conscience.Situations and conditions that always violate norms and deviate and occur repeatedly and continuouslywill strengthen these deviations (prostitution). Referring to this perspective, a person can determine his actions to commit a crime, before the individual has concluded that the benefits will be far greater than the risks and losses faced.